Financial Literacy, Attitudes, and Decision-Making: The Mediating Role of Attitudes and Moderating Role of Consumptive Culture - Hutasoit, Ruth Soraya; Panjaitan, Josephin Michael; Nugraha, Kevin Andrian; Tamba, Alexander Apryan; David, Firman (Lentera Ilmu Nusantara, 2025)
In the modern era, young generations face complex financial management challenges due to technological advancements and the widespread consumerist culture. Financial literacy has become a crucial aspect to support rational and sustainable financial decision-making. This study examines the role of financial attitude as a mediator in the relationship between financial literacy and financial decision-making, as well as investigates the influence of consumerist culture as a moderating variable. Using a causal quantitative approach and purposive sampling of 110 respondents, data were collected through questionnaires and analyzed with PLS-SEM using SmartPLS 3.0. The results show that financial literacy positively affects financial attitude and financial decision-making, with financial attitude mediating this relationship. Although consumerist culture has not yet shown a strong moderating effect, it remains an important factor in the financial behavior of young generations. These findings emphasize the importance of developing financial education programs that not only enhance knowledge but also foster positive attitudes and critical awareness of consumerist culture to support wiser and more sustainable financial decision-making. Furthermore, this study enriches financial literacy scholarship by highlighting the contextual influence of consumerist culture on young generations, thereby advancing the discourse on sustainable financial behavior.